Progress on the Synthesis and Applications of Aminals: Scaffolds for Molecular Diversity - Rippel, Rafael; Ferreira, Luísa M.; Branco, Paula S. (Synthesis, 2024)
Aminals, characterized by a central carbon linking two nitrogen atoms, are versatile building blocks in modern chemistry. This review addresses a literature gap by exploring the synthesis and applications of aminals, with a focus on drug discovery and molecular diversity. Beyond medicinal chemistry, aminals find applications as key components in bioactive compounds and as versatile tools in materials chemistry. The review covers fundamental characteristics, synthetic methodologies, stability, and applications, emphasizing alternative synthetic methods to the well-established aldehyde–amine condensation. This inclusive exploration provides insights into diverse synthetic pathways that expand the versatility of the aminal scaffold.1 Introduction2 The Aminal Group3 Aminal Synthesis3.1 Metal-Free Approaches3.2 Metal-Catalyzed Approaches3.3 Photoredox Methodologies3.4 Via Rearrangements3.5 Via Decarboxylative Coupling4 Aminals as Synthetic Tools5 Synthesis of Aminal-Containing Natural Products6 Aminal-Based Materials7 Conclusions
Keywords: aminals; N,N-acetals; aminal synthesis; aminal stability; nitrogen heterocycles; synthetic tools